Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00429-018-1672-7
|View full text |Cite
|
Sign up to set email alerts
|

18F-F13640 preclinical evaluation in rodent, cat and primate as a 5-HT1A receptor agonist for PET neuroimaging

Abstract: Serotonin 1A receptors are known to play an important role in many psychiatric and neurodegenerative disorders. Currently, all available 5-HT receptor PET radiopharmaceuticals that are radiolabeled with fluorine-18 are antagonists. As agonists bind preferentially to the high-affinity state of receptors, it would be of great interest to develop agonist radioligands which could provide a measure of the functional 5-HT receptors in pathophysiological processes. The 5-HT receptor agonist candidates we recently pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…In contrast, [ 18 F]F13640 showed satisfying properties for neuroimaging. PET studies in rats, cats and non-human primates revealed that it specifically targets 5-HT 1A receptors, and showed a good signal to noise ratio (Vidal et al, 2018a). Moreover, ex vivo autoradiography studies in rat showed that [ 18 F]F13640 was almost ten times more sensitive to competition binding with serotonin than the antagonist [ 18 F]MPPF (Vidal et al, 2018a), thus justifying the current study.…”
Section: Introductionmentioning
confidence: 50%
“…In contrast, [ 18 F]F13640 showed satisfying properties for neuroimaging. PET studies in rats, cats and non-human primates revealed that it specifically targets 5-HT 1A receptors, and showed a good signal to noise ratio (Vidal et al, 2018a). Moreover, ex vivo autoradiography studies in rat showed that [ 18 F]F13640 was almost ten times more sensitive to competition binding with serotonin than the antagonist [ 18 F]MPPF (Vidal et al, 2018a), thus justifying the current study.…”
Section: Introductionmentioning
confidence: 50%
“…This may be due to a more effective competition between agonists as they both compete for receptors in the highaffinity state only. Notably, in vitro [ 18 F]-F13640 binding was markedly reduced by Gpp(NH)p, an agent that switches receptors into an uncoupled state, demonstrating that [ 18 F]-F13640 binds preferentially to G-proteincoupled 5-HT 1A receptors, a property that is consistent with its agonist activity 64 . In contrast, uncoupling of 5-HT 1A receptors from G proteins tends to increase the binding of the antagonist [ 18 F]-MPPF, as previously reported 67,68 .…”
Section: [ 18 F]-f13640 a New Radiopharmaceutical Validated In Humanmentioning
confidence: 84%
“…In order to specifically target 5-HT 1A receptors in their G-protein-coupled functionally active state, we have developed a highly selective 5-HT 1A receptor agonist, [ 18 F]-F13640 64 . F13640, also known as befiradol or NLX-112, is a potent ligand with nanomolar affinity at 5-HT 1A receptors, and exceptional selectivity over a wide range of more than fifty receptor and transporter subtypes 65,66 .…”
Section: [ 18 F]-f13640 a New Radiopharmaceutical Validated In Humanmentioning
confidence: 99%
“…Further study using a full agonist 5-HT 1B receptor ligand that has good uptake into brain by passive diffusion is needed to reinforce this suggestion. Attempts to develop full agonist PET radioligands for imaging the highly homologous 5-HT 1A receptor have also met with limited success [41,42].…”
Section: Discussionmentioning
confidence: 99%